The costs of job loss in Russia - Hartmut Lehmann; Alexander Muravyev; Tiziano Razzolini; Anzelika Zaiceva (Institute for the Study of Labor (IZA), 2010)
This paper is the first to analyze the costs of job loss in Russia, using unique new data from the Russian Longitudinal Monitoring Survey over the years 2003-2008, including a special supplement on displacement that was initiated by us. We employ fixed effects regression models and propensity score matching techniques in order to establish the causal effect of displacement for displaced individuals. The paper is innovative insofar as we investigate as relevant outcomes fringe and in-kind benefits and the propensity to have an informal employment relationship in addition to monthly earnings, hourly wages, employment and hours worked, which are traditionally analyzed. We find that, compared to the control group of non-displaced workers (i.e. stayers and quitters), displaced individuals face a significant income loss following displacement, which is mainly due to the reduction in employment and hours worked. This effect is robust to the definition of displacement. The losses seem to be more pronounced and are especially large for older workers with labor market experience and human capital acquired in Soviet times and for workers with low education. Workers displaced from state firms experience particularly large relative losses in the short run, while such losses for workers laid off from private firms are more persistent. Turning to the additional labor market outcomes, there is a loss in terms of the number of fringe and in-kind benefits for reemployed individuals but not in terms of their value. There is also some evidence of an increased probability of working in informal jobs if displaced. These results point towards the importance of both firm-specific human capital and of obsolete skills obtained under the centrally planned economy as well as to a wider occurrence of job insecurity among displaced workers.
Keywords: J64; J65; P50; 330; costs of job loss; worker displacement; propensity score matching; Russia